Biowaste to biochar: a techno-economic and life cycle assessment of biochar production from food-waste digestate and its agricultural field application - Disni Gamaralalage; Sarah Rodgers; Andrew Gill; Will Meredith; Tom Bott; Helen West; Jessica Alce; Colin Snape; Jon McKechnie (Biochar)
Abstract Biochar has high potential for long-term atmospheric carbon storage in terrestrial environments, contributing to meeting the UK and global greenhouse gas emission reduction targets. This study investigates the greenhouse gas emissions and techno-economics associated with biochar produced from food waste anaerobic digestate using hydrothermal carbonisation followed by high-temperature post carbonisation. Owing to high moisture contents, digestates are challenging to valorise. However, these low-value feedstocks have steady availability with minimal competition for other applications. The study focuses on food waste digestate supply, biochar production, biochar agricultural field application, and transportation activities. Minimising digestate transport through co-locating biochar production facilities with anaerobic digestion displayed greenhouse gas mitigation costs of < £100 tCO2eq−1 (125 USD tCO2eq−1). The 88% stable carbon fraction of the biochar, which is resistant to degradation in soil, is primarily responsible for the effective removal of atmospheric greenhouse gases. This results in net emissions reductions of 1.15–1.20 tCO2eq per tonne of biochar, predominantly due to the long-term storage of durable carbon (1.7 tCO2eq per tonne of biochar). Using 50% of the UK’s projected available food waste digestate by 2030 offers a sequester potential of 93 ktCO2eq p.a., requiring 28 biochar facilities at 20 kt p.a. capacity. Sensitivity analysis emphasises the influence of the gate fee charged to process digestate, highlighting its importance for economic success of the biochar production. Further studies are needed to investigate the potential technology enhancements to reduce fossil-fuel use and provide greater certainty of the co-benefits of biochar application in agricultural soil. Graphical Abstract